Fundamentals Of Business Communication-AF173-202101 - Haro Merino, Ruth Milagros (2021)
Fundamentals of Business Communication offers you the fundamentals of professional development and the tools necessary to gain employment. You crafted resumes, cover letters, and learned to research businesses and industries. In the course we take you inside the organization as a working professional and develop the skills to produce workplace ready documents.